Stories Describing the Lessons Learnt on Developing Business Cases - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
As a contribution to the CCAFS project “Developing, adapting, and targeting portfolios of climate-smart agricultural practices for sustainable intensification of smallholder and vulnerable farming systems in South Asia” this project highlights two stories describing the Lessons Learnt on Developing Business Cases. Story one focuses on business models of small and medium enterprises as mechanism for scaling climate smart agriculture and the second one on young farmers attracted by viable climate smart solutions.